2020
DOI: 10.13106/jafeb.2020.vol7.no7.149
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Cost of Equity: Evidence from Tehran Stock Exchange

Abstract: The purpose of this study was to investigate the impact of corporate governance index on the cost of equity in companies listed on the Tehran Stock Exchange. This study collects data from 975 observations during the period 2012 to 2018 to test the hypotheses using multiple linear regression model for the panel data. In this research, the independent variable of corporate governance index comprises of 27 specific corporate governance attributes. The results of hypothesis testing showed that corporate governance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 46 publications
0
17
0
2
Order By: Relevance
“…MTB is useful for predicting the firms' future growth opportunities. The firm with tremendous growth opportunities is predicted to have a positive relationship with firm performance and Z -score.Leverage: Leverage is measured as the ratio of total debt to total book value of assets (Magerakis and Tzelepis, 2020; Agustia et al , 2020; Kao et al , 2019; Salehi et al , 2020). Leverage is used to examine the firm's ability to deal with business downturns and exposes businesses to the risk of its repayment ability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MTB is useful for predicting the firms' future growth opportunities. The firm with tremendous growth opportunities is predicted to have a positive relationship with firm performance and Z -score.Leverage: Leverage is measured as the ratio of total debt to total book value of assets (Magerakis and Tzelepis, 2020; Agustia et al , 2020; Kao et al , 2019; Salehi et al , 2020). Leverage is used to examine the firm's ability to deal with business downturns and exposes businesses to the risk of its repayment ability.…”
Section: Methodsmentioning
confidence: 99%
“…Leverage: Leverage is measured as the ratio of total debt to total book value of assets (Magerakis and Tzelepis, 2020; Agustia et al , 2020; Kao et al , 2019; Salehi et al , 2020). Leverage is used to examine the firm's ability to deal with business downturns and exposes businesses to the risk of its repayment ability.…”
Section: Methodsmentioning
confidence: 99%
“…It was the first study that examines the relationship between CSR and tax avoidance in an international setting with different legal and institutional environment. Based on these studies, Salehi et al (2020aSalehi et al ( , 2020b examine whether firm risk-taking affects the relationship between managerial entrenchment and CSR in two developing countries (the Iran side and Iraq side) during 2011-2017. The results show that in firms with higher risk-taking, there is a strong relationship between managerial entrenchment and social responsibility both in the Iranian and Iraqi firms.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Meanwhile, another investigation is this area concluded there to be a strong relationship between minimised incentive for a given company to expand their adopted corporate governance mechanisms and subpar financial development and economic climate in their country (Doidge et al , 2007). Salehi et al (2020) found that the quality of corporate governance can lower the rate of capital cost in a sample of 975 observations during the period 2012 to 2018. Faysal et al (2021) also, documented a positive relationship board size and chief executive officer (CEO) tenure in reducing the CEO, and a positive role in audit quality in reducing the CEO in the Iranian context.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%